Investigating the Effect of Tectonic Activities on River Systems (Eastern Slope of Mullah Dagh. Zanjan province) - Zeinab karimi; Davood Mokhtari (تحقیقات کاربردی علوم جغرافیایی)
Rivers are environmental forms that react strongly to changes in their bed, tectonic is the most important factor affecting morphology of the river, causing significant changes in river systems. In this study, using the digital elevation model (DEM), Geographic Information System (GIS) and Global mapper 13, we investigated the effect of tectonic activity on river systems in the eastern slopes of Mullah Daghi, southeast of Zanjan province, this The area is drained by Abhar river. Using the Digital Elevation Model (DEM) in the Arc Gis 10.2 software environment, required maps including geological maps, topography and…, Geological map of 1: 250,000 leaves of Zanjan was used to prepare the fault map. In order to achieve the research objectives, tectonic activity indicators including: are Mountain front sinuosity, basin shape, drainage density, longitudinal gradient of the river, River maze, basin asymmetry, hypersometric integral, the topographic symmetry of the basin and the width of the valley floor to the height. The combination of these indicators is achieved by the tectonic activity index (IAT). The results obtained through the Iat index indicate the activation of tectonic and neotectonic in the watershed of Ardejin and Abhar and the moderate activities in the basin of the zareh bash basin. The impacts of these activities on river systems that are different from the tectonic indexes in the studied basins, such as river meanders(main stream), coniferous formation (Ardejin watershed basin),  tilt watersheds  abhar and Ardejin and  the shape of the basins (Basin elongation zareh bash)